Diphtheria toxin-binding glycoproteins on hamster cells: candidates for diphtheria toxin receptors. - Proia, R L (1979)
Diphtheria toxin-binding glycoproteins of high molecular weight (greater than 100,000) were identified on the surface of lymph node and thymus cells from hamsters, a diphtheria toxin-sensitive species. These diphtheria toxin-binding glycoproteins also interacted with CRM197 protein, which possesses toxin-blocking activity, but not with diphtheria toxoid, fragment A of diphtheria toxin, or cholera toxin, all of which lack toxin-blocking activity. These observations are consistent with the hypothesis that the detected diphtheria toxin-binding glycoproteins are involved in intoxication of cells by this toxin and possibly serve as the plasma membrane receptors for diphtheria toxin.